Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`        Prove that 1/cosec-cot-1/sin =1/sin - 1/cosec + cot`
one year ago

Arun
18694 Points
```							Dear Keshav LHS=1/(cosecA-cotA) -1/sinA
=(cosecA+cotA)/cosec^2A-cot^2A) -cosecA
=cosecA+cotA-cosecA
=cotA
RHS=1/sinA-1/(cosecA+cotA)
=cosecA-(cosecA-cotA)/(cosec^2A-cot^2A)
=cosecA-(cosecA-cotA)
=cotA
LHS=RHS
Regards

```
one year ago
Sankalp Das
25 Points
```							=(cosecx)^2-(cotx)^2=1...=cosecx-cotx=1/cosecx+cotxTherefore,1/cosecx-cotx-1/sinx ...=cosecx+cotx-cosecx=1/sinx-(cosecx-cotx)=1/sinx-1/cosecx+cotx...hp
```
one year ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Trigonometry

View all Questions »

### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution

### Course Features

• 31 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions